Experiences of Male Survivors of Domestic Violence in Kasonga, Kyangwali Refugee Settlement, Uganda - Lilian Abbe (Uganda Christian University, 2025)
This study explores the experiences of male survivors of domestic violence in Kasonga, Kyangwali Refugee Settlement,and Uganda. Despite growing global attention to domestic violence, male survivors particularly in refugee settings remain largely understudied. The research investigates the forms of domestic violence experienced by male refugees, their perceptions of such abuse and the key drivers contributing to its prevalence. Utilizing a qualitative case study design, data were collected through interviews and focus group discussions with 20 male survivors and key stakeholders including local leaders and social workers. Findings revealed that emotional and psychological abuse was the most prevalent form of domestic violence and followed by physical and economic abuse. Sexual abuse was least reported, largely due to stigma and cultural taboos. Many male survivors internalized gender norms that discouraged disclosure, contributing to underreporting and limited access to support services. The study identified key drivers of domestic violence including gender norms, economic strain, substance abuse and the prolonged nature of refugee life. The findings underscore the need for gender-inclusive policies and psychosocial interventions. The study recommends the establishment of male-targeted support systems, community sensitization to challenge harmful norms and capacity-building for service providers. These efforts are essential to promote the wellbeing and protection of male survivors in humanitarian contexts.
Undergraduate research